Burnout among obstetricians and paediatricians: a cross-sectional study from China. Issue 1 (25th January 2019) - Ye, Junying; Wang, Huan; Wu, Hao; Ye, Liaosha; Li, Qi; Ma, Xiang-yu; Yu, Xiaodong; Zhang, Hua; Luo, Xu
Abstract : Objectives: Hospitals devoted to maternal and child health represent unique healthcare institutions in China. Healthcare professionals in these hospitals attend to health services for women and children, and also provide technical services and support for district maternal and children's healthcare as well as family planning. However, few studies have examined occupational burnout among doctors employed in these hospitals. This research addresses the gap in the literature. Methods: A cross-sectional survey of obstetricians and paediatricians from 11 maternal and child health hospitals across China was conducted May through June 2017. A total of 678 people completed a self-administered questionnaire. The survey included questions about demographics, doctor–patient relationships and networks of support as well as characteristics designed to capture the occurrence of burnout, such as emotional exhaustion, cynicism and professional efficacy. T-test, variance and multiple regression analyses were used to examine the data. Results: The research revealed that 56.6% of obstetricians and paediatricians exhibited signs of occupational burnout. Poor doctor–patient relationships and high average number of weekly hours worked contributed to burnout. Additionally, low family support corresponded to physicians' low sense of professional efficacy. Conclusions: Several factors have contributed to occupational burnout among paediatricians and obstetricians at maternal and child health hospitals in China, including lack of family support, poor doctor–patient relationships and heavy workloads.